Tradisi Imlek dalam Perspektif Teologi Inkulturasi Gereja Katolik di Indonesia - Bonifasius; Rinie (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2026)
The Lunar New Year (Imlek) is a cultural tradition deeply rooted in Chinese society, encompassing rich religious, symbolic, and social meanings, particularly concerning life, family, and intergenerational relationships. Within the context of the Catholic Church in Indonesia, Imlek is often perceived ambiguously, situated between a cultural practice and a form of non-Christian religiosity. This article analyzes the Imlek tradition from the perspective of Catholic inculturation theology using contextual theology and cultural theology approaches. This study employs a qualitative method through a literature review of Church documents, theological works, and Indonesian local theological journals. The analysis seeks to explore how cultural traditions such as Imlek can be interpreted within the framework of Catholic theology without compromising doctrinal integrity. The findings indicate that Imlek embodies universal human values consistent with Catholic teachings, including gratitude for life, family reconciliation, social solidarity, and hope for renewal. These values resonate with key Christian principles and pastoral concerns within the Indonesian context. Therefore, Imlek can be understood as a locus of inculturation praxis that enriches Catholic religious experience while avoiding syncretism. This study highlights the importance of an inculturative theological approach in fostering a contextual, dialogical, and culturally rooted Indonesian Catholic Church.